Hierarchy of developmental functions of gram panchayats : an assessment of representatives' response - Singh, S.P. (2002)
To identify the hierarchy of developmental works of GPs, factor analysis model is applied on 61 variables. The paper finds maintenance of natural and human resource inventory, one of the most important groups of development works of GPs. Next to it is human resource development which is followed by income and employment generation, development of infrastructure, arrangement of productive inputs and services, and development of agro-forestry and horticulture. Public accountability comes last in the hierarchical order. The study recommends: maintenance of complete record of human, natural, and physical resources of the village; development of human resource through providing better health, sanitation, and educational facilities; promotion of group entrepreneurship among rural educated youth; strengthening of the Panchayat Udyogs; and training of representatives in various rural management techniques. - Reproduced.
Keywords: Panchayat